The Impact of the Biological Variability or Assay Performance on AMH Measurements: A Prospective Cohort Study With AMH Tested on Three Analytical Assay-Platforms - Bungum, Leif; Tagevi, Julia; Jokubkiene, Ligita; Bungum, Mona; Giwercman, Aleksander; Macklon, Nick; Andersen, Claus Yding; Klausen, Tobias Wirenfeldt; Tørring, Niels; Kumar, Ajay; Skouby, Sven Olaf (Frontiers in Endocrinology, 2018)
This study examined longitudinal, age-related and intra-individual variation in Anti-Müllerian Hormone (AMH) in regular menstruating women and correlate the hormonal levels to the antral follicle count (AFC). The impact of variations on an algorithm for calculation of follitropin-dose for ovarian stimulation was also tested. The study was carried out at a fertility clinic of a tertiary university hospital and has a prospective trial design. Twenty-six healthy women not receiving infertility treatment, sixteen below 30 years and eleven above 35 years participated. Blood sampling for hormonal analysis was done every fifth day throughout three consecutive menstrual cycles, AFC determined with 3-dimentional ultrasound and AMH measured by assays from Beckman Coulter, Roche and Ansh Labs. Outcome measures were maximum and minimum difference in absolute and relative terms per. study subject during the test-period, coefficient of variation (CV) for AMH per cycle and cycle-day and correlation between AMH and AFC. The impact from variable AMH levels on an algorithm calculated follitrophin-delta dose in ovarian stimulation was explored. A significant longitudinal age-independent variation in AMH-levels and coefficient of variation (Cv) per cycle and cycle day was found. A strong correlation between AMH-levels and AFC was confirmed and a case of significant divergence between assays was seen. Variations in AMH had a significant impact on an algorithm calculated dosage of gonadotrophins in ovarian stimulation. The finding of a substantial longitudinal variation in AMH question one recording being sufficient in quantifying gonadotrophins for ovarian stimulation, decision making and prognostication related to infertility treatment and counseling. Occasionally, commercial assays may fail to recognize specific AMH cleavage-products.